Significant roles of synergistic muscles in human redundant and complicated activities - Kouzaki, M. (International Journal of Sport & Health Science, 2005)
In examining the roles of synergistic muscles in human activities, it is impossible to consider these muscles as a single functional unit. It is reasonable to assume that the activities of individual synergists during contractions are different because of the variety of anatomical, biomechanical and physiological features of each muscle. This brief review, therefore, proposes three topics that examine the significant roles of synergistic muscles: 1) task-dependent neural activities are modulated by peripheral afferent activities as well as by the central nervous system; 2) the different roles of mono- and bi-articular muscle activities are essential in controlling human movements; and 3) non-fatigued synergistic muscles compensate for a fatigued muscle via peripheral neural interactions. On the basis of a perspective with an emphasis on synergistic relations, I suggest that the different roles of these muscles, which are neurophysiologically regulated, make it possible to control human activities, and that the concept of the muscle-equivalent model is insufficient because human movements are controlled by both redundant and complex systems.